Культура предпринимательства (религиозно-культурный аспект) - Свистунов, С. (Социология: теория, методы, маркетинг, 2000)
Religious and cultural specific features affect business relations in various world regions, for instance, in West European and Buddhist Confucianism cultures. According to M.Weber, the best way for the modern economy stimulation is Protestantism ethics. However, successful development of certain Far Eastern countries, including Japan, South Korea, Hong Kong, Singapore, gives us an evidence of other efficient systems of ethic and spiritual values stimulating business activity. Multi-confessional Ukraine deals with some problems in business, which are bound up with national spirit orientation toward dynamic development. Considerable part of these problems be -comes more understandable due to the spiritual values analysis.